Basic Ethics of Religious Leaders as Social Adhesives in Society - Harisa Mardiana; Hendrian Yonata; Hendra Attamanoo; Abdul Napudin (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
Religious leaders influence people's lives in increasing community satisfaction and support through their contributions and presence. The expressions of behavior and humility of religious leaders inspire self-transparency, trust, and community satisfaction. The problem in Indonesia today is that many followers or people try to kill their religious leaders. They try to kill religious leaders because religious leaders do not establish trust. In addition, religious leaders do not understand how to apply the basic ethics that form the basis of people's lives. It can divide and violate between communities. This study investigates the problem of attempted murder of religious leaders and finds out the real problem. Almost all religious leaders cannot control their emotions and cannot apply basic ethics in social interactions in society. The research method used is a mixed-method using a questionnaire distributed on Google forms for three months to 247 respondents from all over Indonesia and interviewing eight respondents as a qualitative research method. The results showed that 34.3% of respondents indicated a low level of public trust in religious leaders in people's lives. Religious leaders who can control their emotions in dealing with the community and understand how to apply basic ethics are ideal religious figures. Respondents stated that religious leaders must be consistent and protect their followers; otherwise, people can backfire on religious leaders.